Lasy poza ewidencją – perspektywa ich znaczenia w potencjale zasobów leśnych - Hycza, Tomasz; Wysocka-Fijorek, Emilia (Leśne Prace Badawcze, 2025)
There are over 250 definitions of forests worldwide, resulting in discrepancies in reported forest area, for example to the FAO and UNFCCC. These differences relate to tree height and canopy cover, the size of forest areas, land with woody vegetation used for other purposes, and land temporarily without trees. Forest area can be estimated using national forest inventory data, such as the National Forest Inventory (pl. Wielkoobszarowa Inwentaryzacja Stanu Lasu, WISL) in Poland and statistical methods, or with remote sensing data, such as aerial and satellite images (CORONA, Landsat, Sentinel-2) and airborne laser scanning (ALS). The aim of the study was to compare the area of forest land and various forms of ownership in the Białystok and Krosno Regional Directorates of State Forests, taking into account land with secondary succession, afforested land and land intended for natural succession of various forms of ownership, based on data from the Large-area Forest Inventory (WISL) and CORONA satellite data (from the 1960s) and Sentinel-2 from 2018, based on the studies of Institute of Geodesy and Cartography (Hościło et al., 2020).The area of forest land of all ownership types was 843 450 ha according to BDL data and 1 242 ha according to Sentinel-2 satellite data from 2018 in RDLP Białystok (including forests on former agricultural land) and 561 555 ha and 860 676 ha, respectively, in RDLP Krosno (including forests on former agricultural land). The forest area in Poland has been systematically increasing since the 1960s. Several factors contribute to discrepancies between the registered and actual forest area, including the reluctance of agricultural landowners to reclassify their land as forest, outdated management documentation, forest management operations conducted on land classified as forest in the register, inconsistencies between simplified forest management plans and the register, and the time required to reclassify land afforested under the Rural Development Programme. Currently, there is a lack of analyses aimed at estimating the actual area of forest land in Poland based on remote sensing data, especially in the context of different definitions of forest area for reporting to international organizations such as the FAO and UNFCCC.